Engaging Youth: The Role of Social Media in Promoting Public Accountability in Local Government - Elawati; Victoria Kusumaningtyas Priyambodo (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study investigates the influence of youth engagement through social media on public accountability within local government settings. Focusing on the Province of West Nusa Tenggara, the research employs a convenience sampling approach to explore the dynamics of digital civic participation. Data were obtained via questionnaires distributed to a sample of 210 youth respondents, with subsequent analysis conducted using the Partial Least Squares Structural Equation Modelling (PLS-SEM) technique. The empirical findings reveal that latent engagement, follower engagement, and expressive engagement each exert a positive influence on perceptions of public accountability. These results underscore the critical role of youth as digital stakeholders in enhancing government responsiveness and transparency. More specifically, the study suggests that fostering awareness of accountability mechanisms and promoting inclusive participation among young citizens can contribute meaningfully to the democratic functioning of local governance.